Organizing modernity : new Weberian perspectives on work, organization, and society - Ray, Larry J.; Reed, M. I. (Michael I.) (London ; New York : Routledge, 1994)
This book provides a re-evaluation of Weber's work on the current debates about the institutional and organizational dynamics of modernity, offering interpretations of his work which emphasize the reality of modernity as a dual process.
Book Cover; Title; Contents; List of figures; List of contributors; Weber, organizations and modernity: an introduction; Bringing the text back in: on ways of reading the iron cage metaphor hi the two editions of The Protestant Ethic; Max Weber and contemporary sociology of organizations; Work and authority: some Weberian perspectives; Accounting for organizational feeling; Max Weber on individualism, bureaucracy and despotism: political authoritarianism and contemporary politics; Commerce, science and the modern university; Max Weber and the dilemmas of modernity.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Weber, Max, -- 1864-1920.; Weber, Max, -- 1864-1920; Organizational sociology; Sociologie des organisations; BUSINESS & ECONOMICS -- Negotiating; Organizational sociology; Organisational behaviour